Comamonas testosteroni as the cause of mortality in embryonated chicken eggs of breeding broiler hens in Costa Rica - Chaves-Hernandez, Aida Jeannette (2023)
Mortality of chicken embryos andfirst-week chickens was reported in a commercial incubatorcompany in Costa Rica. Six 1-day-old Cobb chickens and twenty-four embryonated chickeneggs were examined in the Laboratory of Avian Pathology and the Laboratory ofBacteriology of the National University of Costa Rica. Twelve dead-in-shell embryos showedmaceration and were immersed in a putrid, turbid, slightly thick brown liquid. Additionally,the other 12 embryonated eggs had milky yellow-orange content. The livers of thoseembryos had congestion, haemorrhages and multifocal cream foci of necrosis. Granulocyticinfiltration was observed in the bursa of Fabricius, myocardium, liver, lung and kidney. Liversand egg yolks from six embryonated chickens and all 1-day-old chickens were asepticallycollected and cultured. In addition, tissues from six better conserved embryos and all 1-day-old chickens werefixed in buffered formalin and embedded in paraffin. Biochemical andmolecular tests identifiedComamonas testosteronias the cause of the early, middle and lateembryo mortality. As all the eggshells from the sampled embryonated eggs were dirty withsoiled a fecal matter, contamination after manipulating the eggs was considered the sourceof infection.C. testosteroniis an environmental microorganism that has rarely been reportedto cause human disease. To our knowledge, this is thefirst report ofC. testosteronicausingmortality in a hatchery. Cleaning and disinfection using ozone were implemented in thehatchery to eliminate the embryo mortality associated withC. testosteroni.